Different species, life form, and complexity of dead coral head affect the species diversity and density of decapods. (May 2019) - Madduppa, H H; Santoso, P; Subhan, B; Anggoro, A W; Cahyani, N K D; Arafat, D
Abstract: High proportion of dead coral in coral reefs ecosystem are inhabited by a wide variety of associated organisms such as crustacean as a place to live. However, lack of study on the functional of dead corals in high diversity such Indonesian coral reefs. This study aimed to investigate the diversity and density of inhabitant decapod species from two different dead corals with different life form and complexity ( Pocillopora verrucosa and Seriatopora histrix ). A total of 235 individuals consisting of 7 families, 11 genera and 35 species was observed in P. verrucosa. While in S. histrix, a total of 74 individuals consisting of 5 families, 6 genera and 11 species were recorded. Index of diversity (H') on dead coral P. verrucosa for decapods was higher than on S. histrix . Evenness index (E) in both types of dead coral was relatively steady. The domination index (D) for S. histrix was significantly higher than on P. verrucosa . The species density on P. verucosa was significantly higher (25 ± 11.34 ind/L) than on S. histrix (8 ±1.9 ind/L). This study is explaining the complexity of life form on the dead coral seems potentially inhabited by more and diverse decapods.